CHARACTER ANALYSIS OF ENSERA WAT BUJANG SUGITHROUGH MORPHOLOGICAL ANALYSIS THEORY OFVLADIMIR PROPP - Florene Ejot, Masanat; Musdi, Shanat (Aliva Global Research and Development, 2021)
This study analyzes the narrative structure of the intangible culture Iban folklore of a young man named Wat Bujang Sugi in Folklore Ensera Wat Bujang Sugi and a melancholic love story of a brave hero of Iban people in Sarawak. The method that applied in this research is according to Vladimir Propp's morphology theory. The objective of this study is to conduct an academic study on how Vladimir Propp's thirty-one functions and seven spheres of action theory structure uses to abstract the characters that contained in the story of Iban folklore Ensera Wat Bujang Sugi and to analyze the data, the researcher classified the characters into seven spheres of action. It classified the sequence into thirty-one narrative functions in the whole story and the data collection was carried out from the literature review and documentation. The study used descriptive qualitative methods using the method of narrative analysis.